Pengaruh Kualitas dan Fitur terhadap Keputusan Pembelian pada Smartphone Samsung Galaxy A Series (Study Kasus pada Mahasiswa Universitas Darwan Ali di Sampit) - Widia, Amalia Nur; Rayuwanto, Rayuwanto (Universitas Darwan Ali, 2021)
This study aims to determine the effect of the quality and features possessed by smartphones on the purchase decision of the Samsung A Series. The population of this study was Darwan Ali University students and as many as 80 students became the research sample using random sampling. Multiple linear regression analysis will be used because the regression model is free from multicollinearity, normality, and heteroscedasticity. The results of this study indicate that quality and features have a positive and significant effect on purchasing decisions. Quality and features can describe the decision to buy a smartphone by 30.7%.